Experience of Railway Transport Engineers’ Training in the Leading Educational Institutions of Ukraine at the Beginning of the 20th Century - Shargun, T. (Problems of Engineer-Pedagogical Education, 2018)
In the article the training status of the railway transport engineers in Ukraine is researched, the analysis of forms and methods of specialists’ vocational training for the railway branch at the beginning of the 20th century at the example of the leading higher educational institutions is carried out. It was established that in that period in Ukraine the improvement of forms and methods of railway transport engineers’ training was based on that time achievements of vocational schools pedagogics, on the railway branch requirements and first of all was concerned: optimisation the integral inclusion the practical training system for students in the educational process; duration of engineers’ vocational training for the railway branch; differentiated approach to the award of educational qualification grades and degrees; the introduction of subject studying system; organisation of the scientific and technological circles work; organisation of libraries and their providing with literature; sending the graduates abroad for budget account with the aim of knowledge improving etc.